The cost of comfort - Lachs, John (American philosophy., 2019)
Philosopher John Lachs observes that humans today live lives of comfort but also sees that these comfortable lives come at a cost: our increasing unhappiness. In The Cost of Comfort, Lachs contemplates what humans need in order to live fulfilled lives in today's world.